Elbow conditions: research priorities setting in partnership with the James Lind Alliance. Issue 11 (22nd November 2022) - Singh, Harvinder Pal; Chong, Han Hong; Raval, Parag; Divall, Pip; Rangan, Amar; Bateman, Marcus; Watts, Adam; Phadnis, Joideep; Majed, Addie; Jones, Valerie; Pandey, Radhakant; Gower, Jonathan; et al.
Abstract : Objective: To undertake a UK-based James Lind Alliance (JLA) Priority Setting Partnership for elbow conditions and be representative of the views of patients, carers and healthcare professionals (HCPs). Setting: This was a national collaborative study organised through the British Elbow and Shoulder Society. Participants: Adult patients, carers and HCPs who have managed or experienced elbow conditions, their carers and HCPs in the UK involved in managing of elbow conditions. Methods: The rigorous JLA priority setting methodology was followed. Electronic and paper scoping surveys were distributed to identify potential research priority questions (RPQs). Initial responses were reviewed and a literature search was performed to cross-check categorised questions. Those questions already sufficiently answered were excluded and the remaining questions were ranked in a second survey according to priority for future elbow conditions research. Using the JLA methodology, responses from HCP and patients were combined to create a list of the top 18 questions. These were further reviewed in a dedicated multistakeholder workshop where the top 10 RPQs were agreed by consensus. Results: The process was completed over 24 months. The initial survey resulted in 467 questions from 165 respondents (73% HCPs and 27% patients/carers). These questions were reviewed and combined into 46 summary topics comprising: tendinopathy, distal biceps pathology, arthritis, stiffness, trauma, arthroplasty and cubital tunnel syndrome. The second (interim prioritisation) survey had 250 respondents (72% HCP and 28% patients/carers). The top 18 ranked questions from this survey were taken to the final workshop where a consensus was reached on the top 10 RPQs. Conclusions: The top 10 RPQs highlight areas of importance that currently lack sufficient evidence to guide diagnosis, treatment and rehabilitation of elbow conditions. This collaborative process will guide researchers and funders regarding the topics that should receive most future attention and benefit patients and HCPs.